TOOLS OF REGULATION OF ENTREPRENEURSHIP IN KAZAKHSTAN - B.T. Aimurzina,; M.Zh. Kamenova,; Zh.E Nurgaliyeva,; A.T. Omarova, (Academic Journal of Physical and Chemical Sciences, 2019)
In the article considered the modern state of small and midsize businesses in a republic, the analysis of problems retentive his development is conducted, authorial vision of their decision is presented. Authors investigate the sources of the financial providing of development of enterprise, problem of their insufficiency, absence of stimuli for realization. On the basis of analysis of entrepreneurial activity in Kazakhstan in the last few years conclusions are set forth and to recommendation for perfection of instruments of adjusting of enterprise in Kazakhstan, a prognosis is given on further development of small business. It is marked authors, that if to create all corresponding terms providing complex support of enterprise on national and regional levels, increases of level of her financial providing, then these events will result not only in becoming and development of small and midsize businesses but also to the increase on this basis of efficiency of the Kazakhstan economy on the whole.